Pengaruh Edukasi Media Audiovisual Terhadap Perilaku Menjaga Kesehatan Gigi dan Mulut Siswa Sekolah Dasar SDN 252 Nikkel Sorowako - Jumianti Jumianti; Yusriani Yusriani; Abdul Gafur (Jurnal Ners, 2026)
Health in early childhood is a predictor of oral health as they age, and oral health is a crucial factor influencing overall health. Therefore, providing early education and intervention is crucial. The high prevalence of dental and oral health problems in school-aged children, the low effectiveness of conventional educational approaches, and the importance of early habit formation make the need for innovative approaches to dental health education urgent. This study presents a novelty in the form of audiovisual educational media, specifically designed for elementary school children in the context of SDN 255 Nikkel Sorowako, East Luwu Regency. This approach has not been widely used in an integrated manner in health promotion programs in areas with specific social and environmental characteristics, such as mining industrial areas. Furthermore, this study not only evaluates knowledge but also focuses on changes in children's actual behavior dental health status. Therefore, it is expected to provide scientific and practical contributions to the development of health education models. This study used a Pre-Experimental Design with a one-group pretest–posttest design. The research sample was selected using a total sampling technique, in which the entire population was included as the sample. The total population consisted of 40 students, comprising 20 students from class 5A and 20 students from class 5B. Data analysis was performed using statistical tests. The conclusion of this study is that there is a significant difference in students' oral health behaviors before and after receiving education. Therefore, it is recommended that SDN 252 Nikkel Sorowako establish cooperation and collaboration with relevant agencies such as community health centers or dental health professionals in implementing education.